Propriedades físicas do solo em áreas comerciais produtoras de grãos no município de Manoel Viana- RS - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The sustainability of the productive system is linked to the preservation of the physical quality of the soils over time. Therefore, it is necessary to use appropriate management practices that favor the formation and preservation of the soil structure at levels of compaction adequate to the development of the plants. The physical quality of agricultural soils may be affected by the management system, due to changes depending on the time of land use and soil and climatic conditions. Sandy soils are more susceptible to nutrient loss and erosion, presenting greater degradation potential when inadequately managed. This study aims to evaluate the spatial variability of soil physical properties in commercial grain producing areas, located in the municipality of Manoel Viana, RS. The soil physical atributes evaluated were density, total porosity, macroporosity, microporosity, hydraulic conductivity and resistance to penetration. The results found in this study allow to state that almost all the analyzed areas behaved in a similar way with respect to the evaluated parameters and 71% of the layers are superior to the critical value of density for soils of medium texture (20 to 55% of clay).
Keywords: Engenharia agrícola; Propriedades físicas do solo; Manejo do solo; Densidade do solo; Agricultural engineering; Soil physical properties; Soil management; Soil density; CNPQ::CIENCIAS AGRARIAS